Hybrid Resource Modeling and Scheduling Platform Based on Multisource Cooperation for Cyber-Physical-Human System - Jianyong Zhu (Hindawi Limited, 2021)
Cyber-Physical-Human System (CPHS) is receiving increasing attention as an interrelated system that integrates computing, physical, and human resources. Different from existing computing paradigms, CPHS generally comprises heterogeneous software and hardware resources from multiple resource providers and allows interaction among them. The existing research on resource scheduling either focuses on traditional computing resources without consideration of physical environmental factors or is limited to specific application fields, making it difficult to promote and apply across domains. In this paper, we design and implement an application-independent CPHS resource scheduling platform based on a self-defined hybrid resource model. The platform provides a complete instantiation environment for all kinds of CPHS resources and their interactions and supports flexible customization of various resource scheduling strategies. We have injected several different resource scheduling policies into this platform, and the execution results are in line with expectations. The platform is extended to be implemented based on mainstream technologies that have been widely practiced, and the code is open source.